2021
DOI: 10.1002/anie.202016593
|View full text |Cite
|
Sign up to set email alerts
|

Protic Ionic Liquid as Reagent, Catalyst, and Solvent: 1‐Methylimidazolium Thiocyanate

Abstract: We propose anew concept of the triple role of protic ionic liquids with nucleophilic anions:a)aregenerable solvent, b) aB rønsted acid inducing diverse transformations via general acid catalysis,a nd c) as ource of an ucleophile.T he efficiency of this strategy was demonstrated using thiocyanatebased protic ionic liquids for the ring-opening of donoracceptor cyclopropanes.Awide variety of activated cyclopropanes were found to react with 1-methylimidazolium thiocyanate under mild metal-free conditions via unusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 125 publications
0
24
0
Order By: Relevance
“…[22] On the contrary to the original report, wherein the product was poorly purified and almost uncharacterized, we obtained HMimNCS on am olar scale as an analytically pure bench-stable compound and proved its structure by single-crystal X-ray analysis (Scheme 2a). [23,24] Tw oo ther thiocyanate-based PILs Et 3 N•HNCS (3b) [21b] and HTmgNCS (3c)w ere synthesized by the reaction of ammonium thiocyanate with the corresponding amines; triethylammonium thiocyanate was characterized by singlecrystal X-ray analysis (Scheme 2b). We found that the completeness of the cation metathesis can be controlled by an "ammonium test": if the dissolution of the obtained PIL (ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22] On the contrary to the original report, wherein the product was poorly purified and almost uncharacterized, we obtained HMimNCS on am olar scale as an analytically pure bench-stable compound and proved its structure by single-crystal X-ray analysis (Scheme 2a). [23,24] Tw oo ther thiocyanate-based PILs Et 3 N•HNCS (3b) [21b] and HTmgNCS (3c)w ere synthesized by the reaction of ammonium thiocyanate with the corresponding amines; triethylammonium thiocyanate was characterized by singlecrystal X-ray analysis (Scheme 2b). We found that the completeness of the cation metathesis can be controlled by an "ammonium test": if the dissolution of the obtained PIL (ca.…”
Section: Resultsmentioning
confidence: 99%
“…These substrates are too reactive and undergo as ignificant decomposition under the reaction conditions. However,i naless acidic PIL Et 3 N•HNCS,y ields of pyrrolidines 2l and 2m [23] were much better (59 %a nd 56 %), especially when substrates were slowly added to preheated PIL (method B), that allowed minimization of side product formation. Oppositely,c yclopropane 1n,b earing the 4dimethylamino-2-nitrophenyl group,p roduced pyrrolidine 2n in good yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, numerous types of ILs have been known and used in different backgrounds, including task specific-ionic liquids (TS-ILs), room temperature-ionic liquids (RT-ILs), chiral-ionic liquids (C-ILs), switchable polarity solvent-ILs (SPS-ILs), bio-ionic liquids (Bio-ILs), supported ionic liquids (S-ILs), basic ionic liquids (B-ILs), energetic-ionic liquids (E-ILs), neutral-ionic liquids ( N -ILs), metallic-ionic liquids (M-ILs), poly-ionic liquids (P-ILs), and protic-ionic liquids (Pr-ILs) [ 78 , 79 , 89 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 ]. Indeed, such huge variety of ILs is mainly owing to very high diversity in the number of anions and cations and also their own unique thermal and physicochemical features, including ionic conductivity and the ability to mix in organic and inorganic solvents [ 78 , 79 ].…”
Section: Ionic Liquids Structure and Propertiesmentioning
confidence: 99%
“…20 Very recently, Trushkov and co-workers made use of protic ionic liquids with thiocyanate anion (Scheme 1a). 21 With electron-rich DACs, the protic ionic liquid served as a reagent, catalyst, and solvent and converted the threemembered ring into pyrrolidine-2-thiones. This result is noteworthy since the ambident thiocyanate anion attacks the three-membered ring with the less nucleophilic nitrogen atom.…”
mentioning
confidence: 99%